Immunological and virological findings in a patient with exceptional post-treatment control: a case report. Issue 1 (January 2023) - Climent, Núria; Ambrosioni, Juan; González, Tània; Xufré, Cristina; Casadellà, Maria; Noguera-Julian, Marc; Paredes, Roger; Plana, Montserrat; Grau-Expósito, Judith; Mallolas, Josep; Alcamí, José; Sánchez-Palomino, Sonsoles; et al.
Summary: Background: Although antiretroviral therapy (ART) is effective in suppressing viral replication, HIV-1 persists in reservoirs and rebounds after ART has been stopped. However, a very few people (eg, elite and post-treatment controllers) are able to maintain viral loads below detection limits without ART, constituting a realistic model for long-term HIV remission. Here, we describe the HIV control mechanisms of an individual who showed exceptional post-treatment control for longer than 15 years. Methods: We report the case of a Hispanic woman aged 59 years with sexually acquired acute HIV infection, who was included in an immune-mediated primary HIV infection trial involving a short course of ciclosporine A, interleukin-2, granulocyte macrophage colony-stimulating factor, and pegylated interferon alfa, followed by analytical treatment interruption. We did the following viral assays: total and integrated HIV-1 DNA in CD4 T cells and rectal tissue, quantitative viral outgrowth assay, HIV-1 infectivity in peripheral blood mononuclear cells and CD4 T-cell cultures and viral inhibitory activity by natural killer (NK) and CD8 T cells. NK and T-cell phenotypes were determined by flow cytometry. HLA, killer cell immunoglobulin-like receptors, Δ32 CCR5, and NKG2C alleles were genotyped. Findings: After ART and immunomodulatory treatment, the person maintained undetectable plasma viral load for 15 years. HIV-1 subtype was CFR_02AG, CCR5 -tropic. We found progressive reductions in viral reservoir during the 15-year treatment interruption: total HIV DNA (from 4573·50 copies per 10 6 CD4 T cells to 95·33 copies per 10 6 CD4 T cells) and integrated DNA (from 85·37 copies per 10 6 CD4 T cells to 5·25 copies per 10 6 CD4 T cells). Viral inhibition assays showed strong inhibition of in vitro HIV replication in co-cultures of CD4 T cells with autologous NK or CD8 T cells at 1:2 ratio (75% and 62%, respectively). Co-cultures with NK and CD8 T cells resulted in 93% inhibition. We detected higher-than-reference levels of both NKG2C-memory-like NK cells (46·2%) and NKG2C γδ T cells (64·9%) associated with HIV-1 control. Interpretation: We described long-term remission in a woman aged 59 years who was treated during primary HIV infection and has maintained undetectable viral load for 15 years without ART. Replication-competent HIV-1 was isolated. NKG2C-memory-like NK cells and γδ T cells were associated with the control viral replication. Strategies promoting these cells could bring about long-term HIV remission. Funding: Fondo Europeo para el Desarrollo Regional (FEDER), SPANISH AIDS Research Network (RIS), Fondo de Investigación Sanitaria (FIS), HIVACAT, Institut d'Investigacions Biomèdiques August Pi i Sunyer (IDIBAPS), CERCA Programme/Generalitat de Catalunya, la Caixa Foundation, and Centro de Investigación Biomédica en Red de Enfermedades Infecciosas (CIBERINFEC). Translation: For the Spanish translation of the abstract see Supplementary Materials section.